The role of Social Media - Altje E. Tuwaidan; Vesty L. Sambeka; Tirsa A. Lumentut; Pearl Loesye Wenas; Jufrina Mandulangi; Yurike S. Lewan; Mikhael C. S. Mangolo; Frans V. Rattu; Alma K. Pongtuluran (Faculty of Economics and Business, University of Mataram, 2025)
This study aims to examine the operational role of Income Audit staff in preparing Daily Revenue Reports (DRR) based on occupancy rates at Radisson Blu Bali Uluwatu Hotel. Adopting a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that Income Audit staff consistently perform key tasks, including verifying night audit records, calculating occupancy benchmarks, and preparing comprehensive audit packs. The Opera Property Management System (PMS) is used to streamline data entry and facilitate revenue classification. Interviews emphasize the strategic value of income auditing in supporting financial accuracy and managerial decision-making. However, challenges such as human error and system failures affect the reliability and timeliness of DRR preparation. Staff mitigate these risks through multi-layered review mechanisms and adaptive responses during operational disruptions, particularly during the COVID-19 pandemic. The study concludes that Income Audit staff play a critical role in maintaining financial integrity and operational accountability in hotel finance. It recommends continuous training and the enhancement of digital infrastructure to improve audit quality and support effective revenue management. These findings contribute to the literature on internal control and performance measurement in the hospitality industry